Effectiveness of Optometric Photo-Therapy in Amblyopia: Optometric Photo-Therapy in Amblyopia - Younus, Malaika; Abbas, Shakila; Muhammad Nadeem, Maryam; Iqrar, Alia; Naseem, Kausar; Bukhari, Ayesha; Anwar, Mahnoor (Pakistan Journal of Health Sciences, 2023)
Anisometropic amblyopia is amblyopia due to difference of ≥1 D refractive error between two eyes. Objectives: To determine effect of optometric phototherapy on Visual Acuity and Contrast Sensitivity in older children with anisometropic amblyopia and to assess frequency of different degrees of amblyopia. Methods: A Quasi Experimental study was carried at Madinah Teaching Hospital and DHQ, Faisalabad. A total of anisometropic amblyopia subjects of both gender with age ranging from 8 to 18 years who had undergone refractive adaptation were included in the study. Other types of amblyopia and subjects who previously got treated for amblyopia were excluded. Subjects were given optometric photo-therapy for 4 weeks with red amber filter and post assessment was recorded. Descriptive and Paired sample t test statistical analysis was done with SPSS version 27.0. Results: 64% of the subjects had moderate amblyopia, 20% had mild amblyopia while only 16% had severe amblyopia. Visual Acuity improved from .4944 ± .19040 to .3552 ± .20390 (p<0.001) while Contrast Sensitivity improved from 1.3980 ± .21529 to 1.5480 ± .21960 (p<0.001) in optometric photo-therapy. Conclusions: Moderate amblyopia had more prevalence in comparison to both mild and severe amblyopia and Optometric Photo-therapy showed improvement of both visual acuity and contrast sensitivity in anisometropic amblyopia.